Blicken i den gustavianska spegeln: Svensk musikvetenskap om tiden under Gustav III - Wallrup, Erik (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2020)
The reign of the Swedish king Gustav III (1771–92) was a productive period musically. It has become one of the main fields of research within Swedish musicology: more than 40 scholarly articles have been published and ten book-length studies have been printed since 1920. In the article, these texts are read from a critical perspective in order to scrutinize the foundation of the research and to analyse its conditions, but also to see if a transgression is possible. If the ethos of Swedish musicology, with its empirical attitude concerning the survey of sources, can be confirmed in many cases, some examples show that there have been important alternatives: the intention of writing the cultural history of the period (especially Walin and Hedwall), the interest in rhetoric during the 1990s, and investigations of nationalism. The shift from a German to an Anglo-American influence can be discerned during the 1950s, and this change can be the reason why a wider cultural approach became obsolete. Yet, responding to the earlier initiatives, it is suggested finally that musicology can and should turn back to the Gustavian era again after a caesura of fifteen years. Recent work within fields such as affectivity, phenomenology and cultural transfer call upon a re-reading of the manifold sources that have been found during a century of research.